Stability result for Lord Shulman swelling porous thermo-elastic soils with distributed delay term - Choucha A.; Boulaaras S.M.; Jan R. (Walter de Gruyter GmbH, 2024)
The Lord Shulman swelling porous thermo-elastic soil system with the presence of a distributed delay term is studied in this work. We will establish the well-posedness of the system and the exponential stability of the system is derived. 2023 the author(s), published by De Gruyter.